The Effect of NPK and Microbial Consortium on Organosulfur Content: Natural Anti-Diabetes and Efforts to Reduce the Psychological Pressure Level of Diabetics - Suryani, Yani (International Journal of Psychosocial Rehabilitation, 2020)
Had been conducted a research about the effect of NPK and the microbial consortium on organosulfur compounds and their effect as antidiabetic. The study was carried out at Vegetable Research Institute (Balitsa) Lembang from October to December 2019. This study used a completely randomized design with 6 treatments and 3 replications on garlic cv. Lumbu Kuning. The observation parameter was organosulfur compounds which were then applied to 6 lab mice with 100% organosulfur concentration. A questionnaire was also distributed to 100 diabetic patients in Bandung City to determine the psychological conditions of the patients before and after knowing the benefits of organosulfur. The analysis showed that the microbial consortium had a good influence on organosulfur enhancement. Organosulfur was able to reduce glucose levels in mice by 78.64%. Diabetic patients experienced a 15% decrease in anxiety after gaining an understanding of the organosulfur effects.